COVID‑19, food insecurity and dietary diversity of households: Survey evidence from Nigeria - Balana, Bedru; Ogunniyi, Adebayo; Oyeyemi, Motunrayo; Fasoranti, Adetunji; Edeh, Hyacinth O.; Andam, Kwaw S. (Springer, 2023)
The policy measures of the government of Nigeria to restrain the spread of COVID-19, particularly in the initial three months (April – June 2020) led to significant disruptions to household livelihoods and food security. We investigate the effects of COVID-19 on food security and dietary diversity of households; focusing on the pathways through which income loss, endowments of wealth, social capital, and safety net programs moderate the severity of households’ food security and dietary diversity. Primary data obtained from a telephone survey of 1,031 Nigerian households were analyzed using ordered logit and negative binomial models. Our results show that income losses due to the COVID-19 restrictive measures had pushed households into a more severe food insecurity and less diverse nutritional outcomes. Regarding wealth effects, livestock ownership significantly cushioned households from falling into a more severe food insecurity amid the pandemic. We found that because of the pandemic’s indiscriminate effect across communities, the potential of social capital as an informal support mechanism might have been eroded to enable households to cope with shocks. Furthermore, safety net programs by the government and NGOs did not provide significant protection to households from falling into severe food insecurity and malnutrition amid the pandemic. We suggest three policy propositions – prioritize investment in local job creation to curb income loss; build the wealth base of households (e.g., land tenure security or livestock) to enhance resilience to shocks; and target safety nets and other social support programs spatially, temporally, and across social groups to enhance the effectiveness of such programs amid shocks.